Patient Skin Dose during Neuroembolization by Multiple-Point Measurement Using a Radiosensitive Indicator - Suzuki, S.; Furui, S.; Matsumaru, Y.; Nobuyuki, S.; Ebara, M.; Abe, T.; Itoh, D. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Although neuroembolization has recently spread quickly, sufficient attention has not been focused on the associated radiation exposure. The purpose of this research was to evaluate the patient's entrance skin dose (ESD) during neuroembolizations in 6 institutions.MATERIALS AND METHODS: This study was approved by all of the 6 institutional review boards, and all of the patients gave informed consent. This study included a total of 103 consecutive neuroembolizations in the 6 institutions. Patient ESDs during the procedures were evaluated by using caps that had 44 radiosensitive indicators adherent to the surface. The patient ESDs were calculated from the color difference of the indicators. To check for effects on the scalp, clinical follow-up was performed at 1-2 days, 2 weeks, and 3 months after the procedure.RESULTS: The averages of total fluoroscopic time, total number of digital subtraction angiography frames, and dose area product were 67.1 ± 41.6 minutes, 883 ± 626, and 257 ± 150 Gy × cm2, respectively. The average maximum ESD for each patient was 1.9 ± 1.1 Gy (range, 0.4–5.6 Gy; median, 1.5 Gy). The average maximum ESDs of each institution ranged from 1.0 to 2.4 Gy. Epilation was observed in 6 patients.CONCLUSIONS: The maximum ESDs during neuroembolizations exceed the thresholds for radiation skin injuries in some cases.